Leaving words to remember : Greek mourning and the advent of literacy - Derderian, Katharine, 1970- (Leiden ; Boston : Brill, 2001)
This volume examines the influence of literacy on the development of different genres of mourning in ancient Greece. It reveals the non-linear development of Greek literacy and offers insight into the ongoing influence of lament in diverse poetic genres.
ACKNOWLEDGMENTS; INTRODUCTION; CHAPTER ONE: The Unspeakable Lament: the Homeric???? and the heroes; CHAPTER TWO: The Archaic Epigram and the Advent of Writing; CHAPTER THREE:???ææata?????ta t?de Case Studies in Classical Mourning; CHAPTER FOUR: The Epitaphios Logos and Mourning in the Athenian Polis; CHAPTER FIVE: Some Conclusions; BIBLIOGRAPHY; GENERAL INDEX; GENERAL INDEX OF GREEK TERMS.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Greek literature -- History and criticism; Death in literature; Funeral rites and ceremonies -- Greece; Mourning customs -- Greece -- History; Greece -- Social life and customs; Written communication -- Greece; Mourning customs in literature; Grief in literature; Literacy -- Greece; Epitaphs -- Greece; Funérailles -- Rites et cérémonies -- Grèce.; Deuil -- Coutumes -- Grèce -- Histoire; Épitaphes -- Grèce.; Grèce -- Mœurs et coutumes; Littérature grecque -- Histoire et critique; Mort dans la littérature.; Communication écrite -- Grèce.; Deuil -- Coutumes, dans la littérature.; Chagrin dans la littérature.; LITERARY CRITICISM -- Ancient & Classical; Epitaphs; Death in literature; Funeral rites and ceremonies; Greek literature; Grief in literature; Literacy; Manners and customs; Mourning customs; Mourning customs in literature; Written communication; Greece; Klaagliederen; Grieks; Grafschriften; Schriftcultuur; Literatura grega clássica (história e crítica); Oraisons funèbres.; Deuil -- Coutumes -- Grèce.; Lamentations -- Grèce.; Élégies grecques -- Thèmes, motifs; Deuil -- Coutumes -- Dans la littérature.; Rites et cérémonies funéraires -- Grèce.; Grèce -- Moeurs et coutumes; Litteratur -- Klassiske litteraturer; Criticism, interpretation, etc; History